Big Data Analytics in Gaza's Higher Education: Identifying and Addressing Key Implementation Barriers - Yousef Yousef (Jurnal Sistem Informasi, 2024)
This research provides an in-depth investigation into the adoption of Big Data Analytics (BDA) technology in higher education institutions (HEIs) in the Gaza Strip, along with a detailed analysis of the barriers to its implementation. Using a quantitative research methodology, data was collected from 305 participants. Principal Component Analysis (PCA) was employed to identify key barriers to BDA, including challenges related to infrastructure, security, resources, knowledge, and data characteristics. The study found that financial constraints, access pricing and conditions, significant investment costs, lack of BDA expertise, operational expenses, experience sharing, and resource development are the main barriers to BDA adoption. Additionally, the study shows that 65.3% of HEIs are using BDA technology, with a BDA readiness score of 66.68%. Regression analysis indicates that barriers related to security, finances, data characteristics, skills, and infrastructure negatively impact BDA practice and readiness. Based on these findings, proactive measures are recommended to address these barriers in the Gaza Strip. These measures include developing government initiatives, upgrading IT infrastructure, enhancing BDA skills, and promoting BDA technology awareness. The research advocates for further exploration of the specific challenges and opportunities faced by local universities and a deeper investigation into the potential benefits of BDA adoption. Overcoming these obstacles and fostering BDA integration could enhance data analysis capabilities, contributing to the growth and competitive strength of the Gaza Strip.